Structural–Interpretive Model of Customer Confusion Management Based on the Internet of Things in the Banking Industry - Balipour Babadi, Vajihe; Rashnoudi, Asghar; Omidi, Fereydoun (Digital Transformation and Administration Innovation, 2026)
The present study was conducted with the aim of developing a structural–interpretive model (ISM) for customer confusion management based on the Internet of Things (IoT) in the banking industry. This research is applied in nature and qualitative in approach, employing thematic analysis and the structural–interpretive modeling method to explain the relationships among the factors influencing customer confusion management. The statistical population consisted of 17 managers and experts from Bank Mellat branches in Tehran, who were selected through purposive and snowball sampling methods. Data were collected using semi-structured interviews and analyzed with MAXQDA 2018 software. The results of the thematic analysis led to the identification of 77 indicators categorized into 14 main components and six key dimensions. These dimensions include sources of confusion, consequences of customer confusion, internet infrastructures, customer characteristics affecting the increase in confusion, organizational learning management approaches for IoT, and organizational factors influencing confusion management. The findings of the interpretive structural model indicated that the organizational learning management approach for IoT has the highest level of influence, while the sources and consequences of confusion occupy the lowest level. The results further revealed that employing IoT in the banking industry—through enhancing technological infrastructures, automating service processes, and implementing targeted customer education—can effectively reduce confusion and improve customer experience. Therefore, strengthening organizational learning, developing modern technologies, and increasing informational transparency are regarded as fundamental requirements for the effective management of customer confusion in banks.